Do firm strategies exist? - MacCrimmon, Kenneth R. (Strategic Management Journal, 1993)
The central issues addressed in this paper are what it means for strategies to exist and for strategies to change. The concept of strategy is developed progressively as a coordinated series of actions, having a comprehensive scope, and being conditional on environmental events and actions of others. Strategies can be inferred from decisions as well as being stated by top management and can be described in both structured categories as well as in unstructured terms. The framework is utilized to provide guidelines for studying changes in strategies. An analysis of key empirical studies demonstrates the difficulties in answering the question of whether firm strategies exist.